PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE PADA MATERI BILANGAN PECAHAN DI KELAS V SDN 20 SITIUNG - Filahanasari, Eka; Amatulloh, Afifah; Novitasari, Ana (Dharmas Education Journal (DE_Journal), 2025)
Mathematics education basically aims to form logical and critical thinking skills. In SDN 20 Sitiung, many students found it difficult to understand the concept of fractions, students who were not focused on learning, educators who only used textbooks and LKS during the learning process, especially in mathematics subjects, and students who considered mathematics to be a boring subject. Therefore, interesting learning media are needed, especially in class V of SDN 20 Sitiung on the material of fractions, so that students are more interested and find it easy to learn and understand the subject matter independently. One alternative that can be applied is the development of learning media in the form of puzzles. This type of research uses research and development which is more often called Research and Development (R&D) using the ADDIE development model which consists of five stages, namely Analyze, Design, Develop, Implementation, Evaluate. The results of the validation of the puzzle learning media on the fractional number material by 4 validators consist of five aspects that are assessed, the overall average of the assessment of the five aspects has a score of 0.813% with a valid category. The practicality test from educators got a score of 100% with a very practical category and from students got an average percentage of 88% categorized as very practical so that it can be used and can be applied in Elementary Schools (SD). While the results of the effectiveness test got an average of 90.5% effective. So it can be concluded that this V meets the criteria of valid, very practical, and effective so that this puzzle learning media is worthy of use in the learning process